Ten Tips for Encouraging the Use of Your Pine Plantations By Game Species - Holly K. Ober; Stanton Rosenthal; William Sheftall (EDIS, 2010)
WEC273, a 4-page fact sheet by Holly K. Ober, Stanton Rosenthal, and William Sheftall, provides brief tips for making pine plantations more suitable for game species. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, December 2009.